Rediseño y construcción de un banco didáctico para la medición experimental de perfiles de levas radiales y cilíndricas (2023)
Mechanical engineering students from the Antonio Nariño University, Ibagué campus, require practices in each of the study plan areas, and for the Mechanical Design subject it is essential, especially in the cam design, to have a tool that allows students to apply in a practical way the concepts seen in class, in a simple and intuitive way.